2015
DOI: 10.1152/ajpgi.00422.2014
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and alanyl-glutamine promote crypt expansion and mTOR signaling in murine enteroids

Abstract: Moore SR, Guedes MM, Costa TB, Vallance J, Maier EA, Betz KJ, Aihara E, Mahe MM, Lima AA, Oriá RB, Shroyer NF. Glutamine and alanyl-glutamine promote crypt expansion and mTOR signaling in murine enteroids. Am J Physiol Gastrointest Liver Physiol 308: G831-G839, 2015. First published March 19, 2015; doi:10.1152/ajpgi.00422.2014.-L-Glutamine (Gln) is a key metabolic fuel for intestinal epithelial cell proliferation and survival and may be conditionally essential for gut homeostasis during catabolic states. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…Furthermore, combined GH and GLN treatments have been found to have synergistic effects on intestinal adaptation in animal studies and in patients with SBS . Although these viewpoints have been widely accepted for many years, the impact on ISCs has been reported only in very few studies . In our research, in vitro and in vivo studies revealed that GH treatment enhances the formation of crypt organoids, increases ISC stemness markers in the intestinal organoids, and increases proliferation.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Furthermore, combined GH and GLN treatments have been found to have synergistic effects on intestinal adaptation in animal studies and in patients with SBS . Although these viewpoints have been widely accepted for many years, the impact on ISCs has been reported only in very few studies . In our research, in vitro and in vivo studies revealed that GH treatment enhances the formation of crypt organoids, increases ISC stemness markers in the intestinal organoids, and increases proliferation.…”
Section: Discussionmentioning
confidence: 52%
“…[1][2][3][4]10,12 Although these viewpoints have been widely accepted for many years, the impact on ISCs has been reported only in very few studies. 36 In our research, in vitro and in vivo studies revealed that GH treatment enhances the formation of crypt organoids, increases ISC stemness markers in the intestinal organoids, and increases proliferation. In addition, GH upregulates the expression of lysozyme and villin, indicating an increased number of Paneth cells and enterocytes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Trials using specific amino acids such as arginine and glutamine,34 proteins such as lactoferrin and lysozyme,35 and legumes as supplementary foods for children during their period of weaning36 all have potential for demonstrating improvements in EED and stunting. Foods, either genetically modified or natural, that are high in growth factors that reduce apoptosis, enhance enterocyte proliferation and stimulate villous growth are prime targets for investigation.…”
Section: Reducing Eed With Novel Water Sanitation and Hygiene And Numentioning
confidence: 99%